Study of Some Structural and Optical Properties of AgAlSe2 Thin Films - Khudayer, Iman H.; Hussien, Bushra H. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
The structural properties of ternary chalcopyrite AgAlSe2 compound alloys and thin films that prepared by the thermal evaporation method at room temperature on glass substrate with a deposition rate (5Â±0.1) nm s-1 for different values of thickness (250,500 and 750Â±20) nm, have been studied, using X-ray diffraction technology. As well as, the optical properties of the prepared films have been investigated. The structural investigated shows that the alloy has polycrystalline structure of tetragonal type with preferential orientation (112), while the films have amorphous structure. Optical measurement shows that AgAlSe2 films have high absorption in the range of wavelength (350-700 nm). The optical energy gap for allowed direct transition were evaluated, which decreases with film thickness increasing, i.e. it decreases   from 2.5 eV to 2.2 eV when thickness varies from 250Â±20 nm to 750Â±20 nm.